Peranan Akuntabilitas Publik dan Partisipasi Masyarakat dalam Pemberantasan Korupsi di Pemerintahan - KURNIAWAN, TEGUH (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
This article attempts to give the picture concerning the importance of public accountability and citizen participation as one of the instruments to eradicate bureaucratic corruption, seen from various theories. This paper provides equal and adequate understanding of the role of public accountability and citizen participation in the eradication process of corruption and the various efforts that can be done to strengthen it. The results of this literature review shows that the efforts taken to eradicate corruption in Indonesia is still partial and tend not to have a clear design strategy so that in many cases is not able to reduce signicantly the level of corruption that occurred. Besides that, the important role of public accountability and citizen participation in the eradication of corruption has not received much attention as well as has not been thoroughly studied. Therefore we need further study of the various aspects of public accountability and citizen participation in the eradication of corruption in Indonesia.